Critical Condition in CuInAlSe2 Growth of Solar Cell Absorber - Sujarwata Sujarwata; Fianti Fianti; J.Y. Jung; S.H. Lee; K.H. Kim; M.I. Amal (Universitas Ahmad Dahlan, 2016)
CuInAlSe2 (CIAS) thin films were prepared using pulsed laser deposition (PLD) and selenization. The PLD process utilized a certain kind of stacking order to deposit elemental films on glass substrates, layer by layer, for precursor preparation. They were designed to be Al- and Cu-deficient and selenized using two different heat treatment steps. According to its precursor compositional ratio, stacking order, and heat treatment, each CIAS film showed different properties and a critical condition. The crystalline phases, compositional ratio, morphology, and optical-electrical properties of the CIAS films are discussed here.